PROGRAM WEBSITE RESERVASI HOTEL SECARA ONLINE HOTEL CAPITOL PLAZA SUKABUMI - Diana Tanu Wijaya; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
For one development of technology is internet, a global online network without limit that serve a million kind of information. With internet is make simple to all people to search important information that all needed. For internet there’s a website that a static page can accessed during connected into internet network. Hotel Capitol Plaza is a hotel locate in the city of Sukabumi, West Java. This hotel is still use the running manual system. Therefore Hotel Capitol Plaza need the computerization system like website. This case that Hotel Capitol Plaza want to reach as hotel that run for section room reservation service. Therefore is need to create online reservation hotel. Implement with System Development Life Cycle. This Reservation Online Website use HTML,PHP, and MySQL. Keyword Hotel, Capitol Plaza, Sukabumi, West Java, SDLC, HTML, PHP, MYSQL